1993
DOI: 10.1111/j.1399-6576.1993.tb03765.x
|View full text |Cite
|
Sign up to set email alerts
|

Cervical epidural steroid injection for cervicobrachialgia

Abstract: Fifty patients with chronic resistant cervicobrachialgia were randomly divided into two groups. Twenty-five patients (group A) were treated with cervical epidural steroid/lidocaine injections and 17 patients (group B) were treated with steroid/lidocaine injections into the posterior neck muscles. Another eight patients from group B were excluded from the study because they had started the process of litigation of insurance claims and their subjective analysis of pain relief might therefore not be trustworthy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(104 citation statements)
references
References 11 publications
2
99
0
3
Order By: Relevance
“…This study compared them to intramuscular corticosteroid injections, with superior results observed in the interlaminar injection group [8]. This finding supports the theory that a more target specific and higher concentration of corticosteroids produces better results.…”
Section: Comparative Benefits and Riskssupporting
confidence: 75%
See 3 more Smart Citations
“…This study compared them to intramuscular corticosteroid injections, with superior results observed in the interlaminar injection group [8]. This finding supports the theory that a more target specific and higher concentration of corticosteroids produces better results.…”
Section: Comparative Benefits and Riskssupporting
confidence: 75%
“…Surprisingly, this practice has never been shown to benefit patients with cervical radiculopathy. As detailed above, intramuscular corticosteroid administration is inferior to interlaminar epidural injection based on a single randomized trial [8]. Another well-designed placebo controlled randomized trial found that oral corticosteroids were no better than placebo in the treatment of lumbar radiculopathy [94].…”
Section: Alternativesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 Prospective and retrospective studies have been completed with limited patient enrollment, 7,8 widely varying results, and varying time periods of followup. 4,[9][10][11][12][13] Although studies have been completed that attempted to link successful outcomes to findings on cross-sectional imaging, 14 EMG findings, 7 or diagnostic root blocks, 7 most patients are referred for therapeutic cervical epidural injections with a variety of clinical, radiographic, and electrophysiologic data.…”
Section: Discussionmentioning
confidence: 99%